Rhodocodon jackyi (Asparagaceae, Scilloideae), a new species from Madagascar related to R. urgineoides - Knirsch, Walter; Martínez-Azorín, Mario; Brudermann, Andreas; Pfosser, Martin; Wetschnig, Wolfgang (Phytotaxa, 2016)
Rhodocodon jackyi is here described as a new species related to R. urgineoides, they both belonging to Rhodocodon subg. Urgineopsis. The new species shows a distinct syndrome of morphological characters, such as the deciduous, large, spirally arranged, synanthous leaves; the multiflowered, lax, secund raceme; flower pedicels 12‒22 mm long; and white, campanulate, nodding flowers. Moreover, R. jackyi shows a distinct ecology and biogeography.